The Influence of Content Marketing and E-Wom On Social Media On Purchasing Decisions at Kopi Roemah Kesambi - Ninik Isropiani Nurohmah; Elsa Nurul Aliana; Soesanty Maulany (PT. Publikasiku Academic Solution, 2024)
The development of the café business in Indonesia is currently growing rapidly, thus business people must be able to take advantage of the use of social media starting from promoting business on social media such as on Instagram and TikTok applications. Where users can share user experiences on their respective account channels.This study aims to analyze how marketing communication through Content Marketing and Electonic Word Of Mouth on social media is able to influence purchasing decisions at Kopi Roemah Kesambi.This type of research uses a quantitative methodology approach. The population of this study is an unknown number of Roemah Kesambi Coffee consumers. The data source used is primary data from the questionnaire disseminated. Samples were taken using incidental sampling methods using the Corchan Formula and obtained as many as 100 respondents. The data analysis techniques used are Validity, Reliability, Multiple Linear Regression Analysis and structural models measured using adjusted R square and hypothesis tests using SPSS statistical tool version 22. The results showed that Content Marketing had a positive effect on Roemah Kesambi's Coffee Purchase Decision. Elecronic Word Of Mouth has a positive influence on the purchase decision of Roemah Kesambi Coffee. This research can provide in-depth insight into the factors that influence the purchasing decisions of Roemah Kesambi Coffee consumers. These findings can be an important reference for business people and researchers to develop more effective marketing strategies.